The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s00264-018-3866-2
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide study on the risk of unprovoked venous thromboembolism in non-traumatic osteonecrosis of femoral head

Abstract: The incidence and risk of unprovoked VTE were significantly increased in the non-traumatic ONFH population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In the previous study, the incidences of unprovoked VTE, DVT, and PE were 1.2%, 1.0%, and 0.2%, respectively [20]. Current study found the corresponding incidences were slightly increased to 1.4%, 1.1%, and 0.4%, respectively.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In the previous study, the incidences of unprovoked VTE, DVT, and PE were 1.2%, 1.0%, and 0.2%, respectively [20]. Current study found the corresponding incidences were slightly increased to 1.4%, 1.1%, and 0.4%, respectively.…”
Section: Discussionmentioning
confidence: 54%
“…Short-term or long-term administration of NSAID protected ONFH patients from postoperative VTE was noted in the present study. Also, data from the previous two studies [14,20] have documented that NSAID has the protective effects against not only provoked VTE but also MACCE in patients with nontraumatic ONFH. Although most early researches have shown the use of non-selective NSAID strongly leads to endothelial dysfunction and links to arterial/venous thrombotic complications [27,28], yet more and more recent meta-analyses have challenged the cardiovascular safety issue of NSAID, especially cyclooxygenase-2 (COX-2) selective inhibitor [29,30].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations